THE INFLUENCE OF Pd IMPREGNATION INTO Al-MCM-41 ON THE CHARACTERS AND ACTIVITY FOR BIOGASOLINE PRODUCTION BY CATALYTIC HYDROCRACKING OF FAMEs FROM NYAMPLUNG SEED OIL (Calophyllum Inophyllum) - Hendro Juwono; Triyono Triyono; Sutarno Sutarno; Endang Tri Wahyuni (Indonesian Journal of Chemistry, 2013)
Biogasoline have been synthesized through catalytic hydrocracking reaction against FAMEs compounds (fatty acid methyl esters) obtained from the transesterification of Nyamplung seed oil. The performance of Al-MCM-41 and Pd/Al-MCM-41 as the catalytic hydrocracking was compared. In this research, the influence of Pd impregnation into Al-MCM-41 catalyst on the characters and catalytic activity has been evaluated. The characters determined were crystallinity by using X-Ray Diffractometer (XRD), Si/Al ratio by Inductively Coupled Plasma (ICP), the acidity by pyridine adsorption, the surface area and pore volume by surface area analyzer and the morphology by Scanning Electron Microscopy (SEM). Catalytic activity was examined for hydrocracking of free fatty acid methyl esters (FAMEs) produced from the transesterification of Nyamplung seed oil, by Hydrogen flowing. The research result showed that impregnation of Pd into Al-MCM-41 has been successfully carried out, which did not destroy the structural morphology of the catalyst. It was also discovered that the Pd impregnation could increase Si/Al ratio and the acidity but it leads to decrease in the catalyst surface area and the volume. Furthermore, Pd impregnated Al-MCM-41 showed superior activity compared to Al-MCM-41 for FAMEs hydrocracking. The superiority was indicated by higher effectiveness and yields selectiveness, that were 100% hydrocarbon composed of C9-C18 that was dominated by C12 emerging the gasoline fraction, compared of that by the results used Al-MCM-41 catalyst that were 97% hydrocarbon consisted of C8-C20 with equal abundance.